Mechanically-activated solid-state synthesis of nanoparticles of HfB2, HfC and HfN from partially hydrated hafnium tetrachloride. (16th June 2008) - Barraud, E.; Begin-Colin, S.; Le Caer, G.; Barres, O.; , F. Villieras
Nanocrystalline hafnium diboride, carbide and nitride are synthesised by a two-step process, namely a short mechanical activation step (∼1?2 h) of powder mixtures based on partially hydrated hafnium tetrachloride, ph-HfCl4, and on magnesium, followed by a brief annealing step (∼1 h) of the activated powders in flowing argon at 1100?C. HfCl4 is a by-product of the carbochlorination process of extraction of zirconium from ores. Magnesium has a strong reducing capacity and is insoluble in metallic hafnium. The unsought reaction products may then be eliminated during the additional heat treatment or by further leaching. Mechanically activated powder mixtures of ph-HfCl4 + B and of ph-HfCl4 + B + Mg yield either facetted grains or monocrystalline rods of HfB2 according to the composition of the initial mixtures and to the temperature and duration of the annealing treatment. The mean size of the facetted grains ranges between 100 nm and 300 nm. The growth direction of the rods is along the c-axis. Their mean diameters are around 100 nm and their mean lengths are in the range 500 nm?1 um. Hafnium carbide HfC is directly mechanosynthesised from ph-HfCl4 + Mg + C powder mixtures. A subsequent heat treatment in flowing argon allows to better crystallise the grains of HfC (∼100 nm) and to decompose the intermediate products. Annealing of ground ph-HfCl4 + Mg blends in flowing nitrogen for 1 h at 1100?C yields HfN nanoparticles whose size ranges between 10 nm and 30 nm. Characterisations of powders by X-ray diffraction, thermogravimetric analysis, scanning and transmission electron microscopy, Fourier Transform Infrared Spectroscopy were performed to follow the phase evolution and to clarify the reaction mechanisms.